The Impact of ZIS Fund Management by Lazismu on the Growth and Empowerment of UMKM - Rahmat; Aiyub Anshori (Mabsya: Jurnal Manajemen Bisnis Syariah, 2024)
The management of Zakat, Infaq, and Sadaqah (ZIS) funds plays a critical role in supporting the growth of Micro, Small, and Medium Enterprises (MSMEs) in West Kalimantan, as these funds provide essential capital to businesses with limited access to formal financing. This study explores how Lazismu Kalimantan Barat manages ZIS funds and examines their impact on the development of local MSMEs. Using a qualitative methodology, data were collected through in-depth interviews with ZIS fund recipients. The research focuses on the processes of fund distribution, utilization, and the challenges faced by MSMEs in managing the capital received. The findings reveal that Lazismu has implemented an efficient and transparent process for distributing ZIS funds, facilitating access for recipients. The funds are primarily used to enhance production capacity, improve product quality, and support business operations. Additionally, MSMEs benefit from financial management and marketing training provided by Lazismu. However, challenges in fund allocation remain, indicating the need for more intensive mentorship in financial planning. The study concludes that Lazismu's effective management of ZIS funds has significantly contributed to MSME growth, particularly in production capacity, innovation, and market expansion. Future programs should prioritize in-depth financial training to maximize the impact of ZIS funds and further support MSME sustainability